Pemanfaatan Aplikasi AI dalam meningkatkan Kompetensi Guru KKG PAI Kecamatan Baso - Yuspita, Yulifda Elin; Okra, Riri; Musril, Hari Antoni; Derta, Sarwo; Jasmienti, Jasmienti; Alamsyah, Yudi; Tanjung, Rahmatin Nihmah; Putra, Muhammad Ade (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2023)
The professional competence of a teacher has a crucial role in transferring knowledge to students. Learning media becomes the teacher's main tool in the knowledge transfer process, with impacts that include improving cognitive, psychomotor and effective aspects of students' learning outcomes. To achieve this goal, teacher creativity and innovation in delivering material, both through direct delivery and the use of learning media, are key. One of the innovations that can be developed is the creation of learning media that can foster students' interest in learning independently or with the help of teachers.Learning media, as an intermediary in learning, can be visual or non-visual, such as video, text, and audio known as multimedia. Although technology has developed, not all teachers are able to utilize multimedia in learning. Effective learning design for subjects in elementary school should be able to attract and motivate students in accordance with the learning objectives.